2008
DOI: 10.1111/j.1440-1827.2007.02193.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of sarcomatoid mesothelioma from true sarcoma and sarcomatoid carcinoma using immunohistochemistry

Abstract: Differentiation of sarcomatoid mesothelioma from other sarcomatoid tumors involving the pleura and other structures by light microscopy remains an important diagnostic challenge for surgical pathologists. The purpose of the present study was to investigate the utility of diagnostic immunohistochemistry for differentiating sarcomatoid mesothelioma from its histological mimics: true sarcoma and pulmonary sarcomatoid carcinoma. A total of 39 specimens of mesotheliomas with sarcomatoid components, 43 specimens of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 27 publications
2
59
0
Order By: Relevance
“…Thus, EM-D were epithelioid mesothelioma showing papillotubular pattern, micropapillary pattern, and/or microcystic pattern and EM-LD showing solid nest, trabecular pattern, signet-ring cell-like appearance and/or single cell infiltration pattern. One representative tissue block was used for immunohistochemical confirmation of mesothelioma using positive and negative antibody panels mentioned in our previous publications (21)(22)(23)(24)(25). This study consisted of 81 cases of epithelioid mesothelioma (EM) (61%), 34 cases of sarcomatoid mesothelioma (SM) (25%) and 19 cases of biphasic mesothelioma (BM) (14%).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, EM-D were epithelioid mesothelioma showing papillotubular pattern, micropapillary pattern, and/or microcystic pattern and EM-LD showing solid nest, trabecular pattern, signet-ring cell-like appearance and/or single cell infiltration pattern. One representative tissue block was used for immunohistochemical confirmation of mesothelioma using positive and negative antibody panels mentioned in our previous publications (21)(22)(23)(24)(25). This study consisted of 81 cases of epithelioid mesothelioma (EM) (61%), 34 cases of sarcomatoid mesothelioma (SM) (25%) and 19 cases of biphasic mesothelioma (BM) (14%).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, while desmin and smooth muscle actin are not considered discriminatory markers for sarcomatous mesothelioma, their expression pattern as reported herein has been described in human sarcomatous mesotheliomas. 9 The pericardial, pleural, and peritoneal cavities, internal organs, and tunica vaginalis of the testes are lined by a monolayer of cells termed the mesothelium. The mesothelium functions to provide protection from physical damage and invading pathogens.…”
mentioning
confidence: 99%
“…Definite pathological diagnosis of MM should be based on immunohistochemical reactivity to some markers such as calretinin and thrombomodulin, in addition to the usual hematoxylin-eosin staining (Kushitani et al 2008). Recently, Takeshima et al reported that the diagnosis of MM was suspicious in approximately 15% cases who died of ''MM'' in Japan (Takeshima et al 2009).…”
Section: Discussionmentioning
confidence: 97%